The Effect of Work Environment on Employee Job Satisfaction at the South Sulawesi Transportation Agency - Gaffar, Muh. Aqsa; Akbar, Abdi; Dipoatmodjo, Tenri S. P. (Southeast Asia Journal of Business, Accounting, and Entrepreneurship, 2024)
Penelitian ini bertujuan untuk mengetahui pengaruh positif dan signifikan lingkungan kerja terhadap kepuasan kerja secara parsial dan simultan. Jenis penelitian ini adalah penelitian kuantitatif. Populasi penelitian ini adalah seluruh pegawai Dinas Perhubungan Provinsi Sulawesi Selatan sebanyak 209 orang. Sampel penelitian ini adalah sebanyak 41 orang dari 209 orang. Teknik pengumpulan data dilakukan dengan cara observasi, kuesioner, wawancara, dan dokumentasi. Teknik analisis data yang digunakan adalah regresi linear sederhana. Hasil penelitian setelah data diolah dengan SPSS.19 menunjukkan bahwa terdapat pengaruh yang positif dan signifikan antara lingkungan kerja (X) terhadap kepuasan kerja (Y). This research aims to determine the positive and significant influence of the work environment on job satisfaction partially and simultaneously. This type of research is quantitative research. The population of this study was all 209 employees of the South Sulawesi Provincial Transportation Service. The sample for this study was 41 people out of 209 people. Data collection techniques were carried out by means of observation, questionnaires, interviews and documentation. The data analysis technique used is simple linear regression. The research results after the data were processed with SPSS.19 show that there is a positive and significant influence between the Work Environment (X) on Job Satisfaction (Y). It can be shown through the results of the t test that the work environment on job satisfaction is 0.005 < 0.05 and the t value is 2.898 > t table 1.685. The R Square is 0.177 or equal to 17.7%. Meanwhile, some of it is influenced by other variables outside this regression equation or other variables that are not studied. Based on this description, it can be concluded that the work environment has a positive and significant effect on job satisfaction at the South Sulawesi Province Transportation Service.